DIFFERENCES IN EMPATHY LEVEL BETWEEN JUNIOR AND SENIOR RESIDENTS, FACULTY OF MEDICINE, DIPONEGORO UNIVERSITY, DR. KARIADI HOSPITAL, SEMARANG - Tatyana Santosa; Sigid Kirana Lintang Bhima; Julia Ike Haryanto; Titis Hadiati (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2021)
Background: The doctor-patient relationship has an important role in determining the diagnosis and patient management. In communicating with patients, as a doctor must show high empathy for patients. Therefore, it is important to assess the level of empathy for patients with Junior and Senior residents for patients. Aim: Understand the differences in the level of empathy towards patients with junior and senior residents at the Faculty of Medicine, Diponegoro University in Dr. Kariadi Hospital, Semarang. Method: Observational study with cross sectional design. The total sample size was 99 consisting of 35 junior residents and 64 senior residents. Nominal scale data, namely 35 junior residents and 64 senior residents were analyzed using the Kolmogorov-Smirnov normality test, while the interval scale data, namely the level of empathy, was analyzed using the unpaired t test. Results: Based on the Kolmogorov-Smirnov normality test. data distribution is normal (p = 0.091). In the unpaired t test, there was no significant difference (p = 0.501) between the level of resident education and the value of empathy. Conclusion: There is no significant difference between the education level of residents at the Faculty of Medicine, Diponegoro University in Dr. Kariadi Hospital, Semarang with the value of empathy, but from the value there is a decrease. Keywords: level of empathy; Junior residents; Senior residents; The Jefferson's Scale of Physician Empathy (JSPE).